ELECTORAL VIOLENCE, POLITICAL PARTICIPATION AND DEMOCRATIC CONSOLIDATION IN NIGERIA: 2019 GENERAL ELECTION IN EBONYI STATE IN FOCUS - Ibeogu, Aloysius S; Nwusulor, Jeremiah Chikwado (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
The quest to conduct free and fair election over the years appears to be impossible in Nigeria. Election period has become an opportunity for political thugs to unleash different kinds of mayhem upon their opponents and unsuspecting innocent citizens of Nigerian. The magnitude of violence during election period in Nigeria is actually worrisome, as it has greatly engendered apathy among the citizens especially in electing the right people into leadership positions in the country and by extension constituted a bane towards democratic consolidation. In view of this trend, this paper examines electoral violence, political participation and democratic consolidation in Nigeria with special focus on 2019 general election in Ebonyi State. Frustration aggression theory as propounded by Dollard in 1939 and expanded by Berkowitz in 1969, was adopted as a theoretical guide while content analysis design was extensively used to elicit relevant information necessary for the study through textbooks, online journals, Newspapers, magazines etc. Findings of the paper reveal; that electoral violence has significantly hindered political participation in Ebonyi State; that electoral violence has impacted negatively on good governance, that electoral violence has also hindered several efforts towards democratic consolidation in Nigeria. It was recommended among other things; that law should be enacted to criminalize acts of electoral violence in Ebonyi State; that voter education should be extensively conducted by stakeholders on the implications of electoral violence in democratic consolidation in Ebonyi State, neutrality of the security agencies in the period of elections in Ebonyi State among others.